2010
DOI: 10.1111/j.1365-2222.2009.03418.x
|View full text |Cite
|
Sign up to set email alerts
|

A prostacyclin agonist with thromboxane inhibitory activity for airway allergic inflammation in mice

Abstract: These data suggest that ONO-1301 may suppress AHR and airway allergic inflammation through modulation of DCs, mainly mediated through the IP receptor. This agent may be effective as an anti-inflammatory drug in the treatment of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…AHR was assessed by measuring changes in respiratory resistance in response to increasing doses of inhaled methacholine (MCh) using the Flexivent system (SCIREQ, Montreal, Que., Canada), as previously reported [19] .…”
Section: Airway Responsivenessmentioning
confidence: 72%
“…AHR was assessed by measuring changes in respiratory resistance in response to increasing doses of inhaled methacholine (MCh) using the Flexivent system (SCIREQ, Montreal, Que., Canada), as previously reported [19] .…”
Section: Airway Responsivenessmentioning
confidence: 72%
“…ONO-1301 also has thromboxane-synthase inhibitory activity because of the presence of a 3-pyridine radical. We previously demonstrated that ONO-1301 prevents acute airway inflammation in murine models of allergic asthma through the inhibition of lung dendritic cell functions (10). In the present study, we investigated whether this compound exerted an effect on the alteration of AHR and airway remodeling in a model of chronic asthma.…”
mentioning
confidence: 84%
“…Hayashi et al [88] reported in 2010 that administration of ONO-1301 was more therapeutic for ovalbumin-induced asthma model in mice than beraprost. In addition, Kimura et al [89] tested the hypothesis that ONO-1301SR treatment is effective in suppressing hyperresponsiveness, allergic inflammation and remodelling of the airway.…”
Section: Ono-1301/ono-1301sr Treatment For Extracardiac Pathologiesmentioning
confidence: 99%